Identificação, quantificação e controle de defeitos em monocristais e nanopartículas de TiO2 - Frederico Dias Brandao (2008)
Titanium dioxide (TiO2) has attracted enormous interest in the scientificcommunity in recent years, basically, for the application as a material on electronic devices, photocatalysis and renewable energy. Most part of this interest is associated to nanostructured TiO2 which has energy gap of 3.2 eV and 3.05 eV for anatase and rutile, respectively. For example, the production of H2 by the hydrolysis of water molecule catalyzed by TiO2 has been shown. Other applications of TiO2 are related to dye sensitized photovoltaic cells and the recent discovery of fourth passive element inelectronic circuits, the memristor. For improvement of the material many scientific groups are working on the modification of the properties of the material. In order to understand the material properties a deep knowledge of the intrinsic and extrinsic defects is fundamental. TiO2 is considered to be a non-stoichiometric material with high deficiency in oxygen which leads a n type conductivity. In this way, the defect chemistry of TiO2 has been described in terms of the intrinsic defects titanium interstitial, Tii, and oxygen vacancy, VO. Surface defects are also easilyproduced and are intimately related with photocatalysis. Besides, much controversy exists in the literature about proposed models. In this work, monocristalline and nanostructured samples produced by the solgelprocess are studied by Electron Paramagnetic Resonance (EPR). The interstitial titanium and complexes, extrinsic defects Nb5+, Cr3+ and Fe3+, as well as, surface adsorbed radicals at the surface were characterized. The incorporation and concentration of the defects are controlled by thermal treatments in oxidizing and reducing atmospheres. EPR and X ray diffraction data are correlated and discussed in terms of defect models in bulk and nanoparticles, for both structures of TiO2, anatase and rutile.